1998
DOI: 10.1017/s1355838298980724
|View full text |Cite
|
Sign up to set email alerts
|

More than one way to splice an RNA: Branching without a bulge and splicing without branching in group II introns

Abstract: Domain 6 (D6) of group II introns contains a bulged adenosine that serves as the branch-site during self-splicing. In addition to this adenosine, other structural features in D6 are likely to contribute to the efficiency of branching. To understand their role in promoting self-splicing, the branch-site and surrounding nucleotides were mutagenized. Detailed kinetic analysis on the self-splicing efficiency of the mutants revealed several interesting features. First, elimination of the branch-site does not preclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 41 publications
6
67
1
Order By: Relevance
“…The construct used in this study lacks the internal loop above the branch site, but trans-branching assays show an almost wild-type like activity. These results corroborate with phylogenetic data [9,10] that indeed no crucial branch point determinants are present in the omitted nucleotides and that the length of the helix above the branch adenosine is not important for docking to the other domains and branching…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The construct used in this study lacks the internal loop above the branch site, but trans-branching assays show an almost wild-type like activity. These results corroborate with phylogenetic data [9,10] that indeed no crucial branch point determinants are present in the omitted nucleotides and that the length of the helix above the branch adenosine is not important for docking to the other domains and branching…”
Section: Discussionsupporting
confidence: 89%
“…In the group II intron ai5γ on the other hand, a base paired branch A does not completely abolish branching. [9] In all eukaryotic spliceosome systems investigated to date, a pseudouridine (Ψ) residue opposite of the branchpoint adenosine has been identified. [36,37] NMR structural analyses have shown that this Ψ is responsible for an extrahelical positioning of the branch adenosine in the isolated branch helix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The branch-site consensus sequence is poorly conserved among eukaryotes (Wu & Manley, 1989)+ In group II introns, not only are the base pairs flanking the bulged adenosine poorly conserved among these selfsplicing introns, but the first step of splicing apparently occurs if the branch-site adenosine is involved in a Watson-Crick base pair (Chu et al+, 1998)+ This finding may diminish the importance of a pseudouridine residue in the spliceosome that facilitates bulging of this residue+ However, there are many documented differences between branch-site recognition in group II introns and spliceosomes+ Specifically, the N6 of the branch-site adenosine is the major determinant in recognition in group II introns (Liu et al+, 1997) whereas the N1 is the most important substituent in spliceosomes (Query et al+, 1996)+ Also, a cytosine can be tolerated at the spliceosome branch site, but it is not acceptable as a branch point in group II introns+ These differences suggest a different mode of recognition for the branch site in spliceosomes and group II introns+…”
Section: Conservation Of C35mentioning
confidence: 99%